Antiarrhythmic properties and mechanisms of SGLT2 inhibitors in managing atrial fibrillation patients with metabolic syndrome - Rahmawati, Novi; Rizal, Ardian; Putri, Diana Yuswanti (Heart Science Journal, 2026)
Atrial fibrillation (AF) frequently occurs in patients with metabolic syndrome (MetS), a cluster of cardiometabolic abnormalities including obesity, hypertension, dyslipidemia, and type 2 diabetes mellitus (T2DM), which collectively promote adverse atrial electrical and structural remodeling. These intertwined conditions significantly complicate AF management and contribute to disease progression. Sodium–glucose cotransporter 2 (SGLT2) inhibitors, initially developed as glucose-lowering agents, have demonstrated robust cardiovascular and renal benefits beyond glycemic control. Accumulating clinical evidence from post-hoc analyses, real-world studies, and large meta-analyses indicates that SGLT2 inhibitors significantly reduce the incidence of new-onset and recurrent AF, particularly in patients with MetS and T2DM. Mechanistic studies revealed that the antiarrhythmic effects of SGLT2 inhibitors arise from pleiotropic actions targeting key arrhythmogenic pathways. These include restoration of intracellular Na⁺ and Ca²⁺ homeostasis via inhibition of the Na⁺/H⁺ exchanger and CaMKII signaling, suppression of oxidative stress and inflammation through modulation of NADPH oxidase and NLRP3 inflammasome activity, attenuation of atrial fibrosis by inhibiting the TGF-β/Smad pathway, and improvement of mitochondrial function and bioenergetics through activation of the PGC-1α/NRF-1/Tfam axis. Additional systemic benefits, such as weight reduction, improved hemodynamics, decreased epicardial adipose tissue, and autonomic nervous system modulation, further contribute to atrial electrical stability. This review summarizes current clinical and mechanistic evidence supporting the role of SGLT2 inhibitors as a promising upstream therapeutic strategy for AF prevention and management in patients with MetS.